Reporting of immune-related adverse events in US Food and Drug Administration approvals of immune checkpoint inhibitors - Tapiavala, Shaili; Luo, Chongliang; Shenouda, Mina; Patel, Vaibhav; Davis, Andrew A. (Frontiers in Oncology, 2025)
BackgroundPredicting the occurrence of immune-related adverse events (irAEs) related to immune checkpoint inhibitors (ICI) is complex. Monitoring of irAEs is critical as toxicities cause morbidity and impact quality of life. Thus, we systematically evaluated the patterns and consistency of irAEs reporting in trials leading to US Food and Drug Administration (FDA) ICI approvals.MethodsWe evaluated 75 primary articles from 2011-2021. The authors independently collected data regarding reporting frequency as a binary classification of reported versus not reported and irAE frequency of 24 irAEs classified by the National Comprehensive Cancer Network Version 1.2024 guidelines. Reporting trends and irAE events were analyzed by study year, phase, primary tumor type, and monotherapy versus combination therapy.ResultsAcross the irAEs evaluated, 41.7% were reported in less than 33% of the trials, 16.6% were reported in 34-66% of trials, and 41.7% were reported in 67-100% of trials. The most frequently reported irAEs included diarrhea/colitis (100%), fatigue (99%), and maculopapular rash (93%). Some infrequently reported irAEs included myocarditis (21%), uveitis (17%), and aseptic meningitis (4%). Additionally, certain organ systems were more frequently reported, including gastroenterology (100%) and endocrine (97%), while others, including cardiology (21%) and ophthalmology (17%), were less frequently reported. The reporting of rarer irAEs significantly increased over time.ConclusionOur study demonstrated significant inconsistencies in irAE reporting in the primary literature of trials associated with FDA approvals, particularly for rarer irAEs. Efforts to standardize irAE reporting from clinical trials in the primary literature are needed for more consistent dissemination of information.